O uso de indicadores na gestão das empresas de serviços da cidade produtiva de petróleo e gás do estado da Bahia - Silva, Fábio Martins da (2008)
This thesis seeks investigate how the use of indicators, is helping firms to service the Network Petrobahia to meet targets set in its strategic planning. As the focus of the theoretical framework, the survey sought the main axes of knowledge needed to analyze the results as strategic planning, quality management and information management based on the teachings of Ansoff (1990), Mintzberg (2001), Ackoff (1981), Porter (1989), Ishikawa (1997), Juran (1992), Deming (1990), Falconi (1989) and Kaplan and Norton (1997). To promote the confrontation between theory and practice, the study examined the relationship of the use of performance indicators with the business. The case study presented itself as the most appropriate methodology for this work. As instruments of research, interviews were conducted with managers of 12 companies members of Redepetrobahia: managers and coordinators of the departments of sales, human resources, logistics, and financial services. Thus, it appears that the service companies in the production chain of oil and gas of the State of Bahia using performance indicators as a tool of business management tend to get better results management.